Algorithm design : foundations, analysis, and Internet examples - Goodrich, Michael T. 4 0 16; 1960- Tamassia, Roberto; 5 (Hoboken, NJ : John Wiley & Sons, 2002)
A comprehensive guide to algorithms that discusses design principles, analysis techniques, and examples off the Internet; as well as basic data structures, search trees, skip lists, fundamental techniques, weighted graphs, flow, and other topics; and includes Java code fragments, visual proofs, and more.
Includes bibliographical references and index.
Adult;Adult
Keywords: 2 -- 0; 6; Computer algorithms.;Data structures (Computer science);Algorithms.;Data processing; 20; 2